Screening of Cucumber (Cucumis sativus L.) Genotypes for Resistant Sources under Low Hill Regions of Himachal Pradesh - Rani, Riya; Sharma, Pallavi; Dogra, B. S.; Sharma, Monica; Kumari, Manisha; Dhiman, Shivali (International Journal of Economic Plants, 2025)
The experiment was conducted during June, 2021 to September, 2021 at the Experimental Farm of Department of Vegetable Science, College of Horticulture & Forestry, Neri, Hamirpur, Himachal Pradesh, India with aim to identify downy and powdery mildew resistant genotype in cucumber. Twenty genotypes of cucumber were evaluated in Randomized Complete Block Design during rainy season (June–September), 2021. During periodic survey, downy mildew and powdery mildew diseases recorded in the field. Percent disease index in all genotypes of cucumber for downy mildew and powdery mildew ranged between 9.53–52.77 and 6.78–36.66, respectively. Maximum Percent disease index for downy mildew was observed in LC-C-2-21 (52.77) and minimum in LC-C-9-21 (9.53), whereas maximum Percent diseases index for powdery mildew was observed in LC-C-10-21(36.66) and minimum in Solan Srijan (6.78). Seven genotypes viz., LC-C-4-21, LC-C-6-21, LC-C-7-21, LC-C-9-21, LC-C-12-21, LC-C-14-21, Solan Srijan were found resistant and LC-C-2-21, LC-C-10-21 were susceptible to downy mildew diseases and rest of genotypes were found to be moderately resistant to disease. None of genotype was observed to be immune, resistant and highly susceptible to powdery mildew diseases. Two genotypes were found moderately resistant while ten genotypes were moderately susceptible and eight genotypes viz., LC-C-2-21, LC-C-3-21, LC-C-4-21, LC-C-7-21, LC-C-10-21, LC-C-14-21, LC-C-15-21, LC-C-16-21were susceptible to powdery mildew. From our study, LC-C-9-21 and Solan Srijan genotypes were recommended to farmer for getting higher production under low hill of Himachal Pradesh and to breeder for further resistance breeding programme.